2020
DOI: 10.1186/s12879-020-05456-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns and associated factors of HIV Seropositivity among adults in Ethiopia from EDHS 2016: a spatial and multilevel analysis

Abstract: Background HIV is a major public health issue, especially in developing countries. It is important to track and design successful intervention programs to explore the spatial pattern, distribution, and associated factors of HIV Seropositivity. This study therefore showed the spatial variation of HIV Seropositivity and related factors in Ethiopia. Methods A total sample of 25,774 individual data collected from the 2016 EDHS data were primarily HIV biomarkers, IR, MR, and GPS. Spatial heterogeneity analysis wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
1
15
0
4
Order By: Relevance
“…In addition to Addis Ababa, Dire Dawa, and Adama, the current study identified that the country’s main cities or towns, such as Woldiya, Humera, Kombolcha, Dese, and Kobo, appeared as HIV hot spots. This may be because such places have a higher number of commercial sex workers [ 64 , 65 , 66 ], and some of the cities/towns are transport corridors for truck drivers or long-distance vehicle drivers, e.g.,Adama, Woldiya, and Kobo for trucks coming or going from or to the Djibouti port [ 67 ]. In addition, cities, towns, or generally urban areas are associated with a high rate of HIV infection [ 68 , 69 ] as residents in urban areas have higher population movement due to labor, migration, and trading.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Addis Ababa, Dire Dawa, and Adama, the current study identified that the country’s main cities or towns, such as Woldiya, Humera, Kombolcha, Dese, and Kobo, appeared as HIV hot spots. This may be because such places have a higher number of commercial sex workers [ 64 , 65 , 66 ], and some of the cities/towns are transport corridors for truck drivers or long-distance vehicle drivers, e.g.,Adama, Woldiya, and Kobo for trucks coming or going from or to the Djibouti port [ 67 ]. In addition, cities, towns, or generally urban areas are associated with a high rate of HIV infection [ 68 , 69 ] as residents in urban areas have higher population movement due to labor, migration, and trading.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the family sold this type of food item and shifted to other low-cost items, such as serials, to earn more money and provide enough food for their family. Most SSA countries suffer from malnutrition in various forms, including stunting, wasting, underweight, and anemia 50 .…”
Section: Discussionmentioning
confidence: 99%
“…(6) Spatiotemporal cluster analysis Spatiotemporal cluster analysis was applied to the analysis of disease distribution and transmission (Hailu et al, 2020;Rau et al, 2020).…”
Section: Epidemic Analysis Methods Based On Gismentioning
confidence: 99%
“…Spatiotemporal cluster analysis was applied to the analysis of disease distribution and transmission (Hailu et al., 2020; Rau et al., 2020). In this study, spatiotemporal cluster analysis was used to determine whether regions and periods showed significant clustering of PPR outbreaks.…”
Section: Methodsmentioning
confidence: 99%